2010
DOI: 10.1051/0004-6361/201014762
|View full text |Cite
|
Sign up to set email alerts
|

Radiative emission of solar features in the Ca II K line: comparison of measurements and models

Abstract: Context. The intensity of the Ca II K resonance line observed with spectrographs and Lyot-type filters has long served as a diagnostic of the solar chromosphere. However, the literature contains a relative lack of photometric measurements of solar features observed at this spectral range. Aims. We study the radiative emission of various types of solar features, such as quiet Sun, enhanced network, plage, and bright plage regions, identified on filtergrams taken in the Ca II K line. Methods. We analysed full-di… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 45 publications
(117 reference statements)
2
27
2
Order By: Relevance
“…Skumanich et al (1984) showed that the center-to-limb variation of the Ca II K emission (which hereafter is used as a representation of the summed emission in the H and K lines, see Radick et al 1998) is the same for the quiet Sun and faculae. This was confirmed by later measurements (see, e.g., Ermolli et al 2007Ermolli et al , 2010. Thus one can write…”
Section: Chromospheric Activitysupporting
confidence: 68%
See 1 more Smart Citation
“…Skumanich et al (1984) showed that the center-to-limb variation of the Ca II K emission (which hereafter is used as a representation of the summed emission in the H and K lines, see Radick et al 1998) is the same for the quiet Sun and faculae. This was confirmed by later measurements (see, e.g., Ermolli et al 2007Ermolli et al , 2010. Thus one can write…”
Section: Chromospheric Activitysupporting
confidence: 68%
“…Functions C HK (μ) and C Q cont (μ) describe the CLV of the HK and continuum fluxes. The HK flux and its CLV are strongly affected by the effects of non-local thermodynamical equilibrium (see, e.g., Ermolli et al 2010), which are not taken into account in the spectra employed by the SATIRE model (Unruh et al 1999). Therefore, instead of taking the theoretical CLV resulting from SATIRE, we employed quadratic polynomial parameterizations (as a function of the heliocentric angle cosine μ) of the CLV from Skumanich et al (1984), who employed several observational datasets to define them.…”
Section: Chromospheric Activitymentioning
confidence: 99%
“…Images taken between September 1997 and January 2012 have been processed and segmented to identify different features on the solar disc as described by Ermolli et al (2010). The seven classes of atmospheric features proposed by Fontenla et al (2009) are considered.…”
Section: Oarmentioning
confidence: 99%
“…Therefore, the Ca II K line emission can be used as a good proxy of the LOS magnetic flux density over the whole solar disk (e.g. Ermolli et al 2010, and references therein). The H α line at 656.28 nm has been also widely employed for studying the solar chromosphere, which was defined as what is seen in this line (Lockyer 1868).…”
Section: White-light Facular Indicesmentioning
confidence: 99%